On the notion of “owning a forest”: Ideological awareness and Genre-based Pedagogy in university critical literacy - Guerra-Lyons, Jesús David; Mendinueta, Nayibe Rosado (DELTA: Documentação e Estudos em Linguística Teórica e Aplicada, 2021)
This paper discusses a collaborative action research project integrating a focus on ideological awareness with genre-based pedagogy in the university literacy classroom. Through explicit instruction on the argumentative genre and refl ection on the linguistic correlates of neoliberal ideology, we guided students in developing enhanced awareness of neoliberalism and its infl uence on environmental policy. In the independent writing stage, students’ argumentation revealed critical stances towards neoliberalism and adequate command of the target genre. The paper closes with general refl ections and recommendations for the adoption of an explicitly critical approach in university literacy education.